Kepatuhan Functional Requrements Hak Akses pada Electronic Records Management System Arteri. - Achmad Fachmi; Nina Mayesti (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2021)
This Research discusses the compliance of the Electronic Records Management System (ERMS) on the Principles and Functional Requirements for Records in Electronic office environments (ICA-REQ) Module Two related to access control functions in one of the main categories is maintain. One of the ERMS management records, namely Arsip Elektronik Terintegrasi (Arteri) is based on open-source. Arteri is the ERMS for managing web-based electronic records to facilitate records management. Therefore, this research aims to determine whether the arteries meet the ERMS standard on the ICA-REQ regarding access control. So, the results of the analysis can be used as input for developers and users to conduct further evaluation and improvement. This research used a qualitative approach with literature study and made observations on Arteri as the object. On analysis it was found that Arteri only fulfilled 12 of the 17 mandatory access control function requirements.